Arbeitsbündnisse und Kooperation als Formen praktizierter Anerkennung – Diversity und institutionelle Sensibilität - Algermissen, Ulf (International Dialogues on Education Journal, 2016)
The article addresses the requirements of a pedagogy which acknowledges a kind of multiplicity that not only aims at meeting associated general and specific pedagogical and therapeutic challenges theoretically but also successfully puts it into practice. The discussion focuses on conditions for the respective pedagogical work of those involved: cooperation, acting with a plan, development of trust, awareness and differentiated consideration of the actual dispositions of learners. In this context the foundations of reflection, institutional development and professionalization of pedagogical work are discussed.